Network monitoring application for IPV6 network with IPSEC - Aashique, Mohammad Aashraful (2005)
With the increasing need for fast and reliable network connectivity, there has been an exponential rise in the number of local area networks. The networks are becoming bigger and more complex. To ensure that networks function efficiently, network monitoring and management is needed to detect any malfunctioning and take corrective measures. Network monitoring is also useful for observing network performance and traffic patterns, for planning changes and upgrades. In this thesis, the network monitoring application having Graphical User Interface (GUI) for IPv6 network that will support IP Security. The Linux Router will check the all IP packets from the network, if IP packets has IPSec bits then its secured otherwise it will discard. The IPSec-Policy-MIB which will be take the filtering log to the database.The GUI will show the filtering log to the monitoring system. The router will intercept packets from network interfaces flowing through it and the monitoring application will display the appropriate information.